Efektivitas Layanan Transaksi Qris Pada Pelaku UMKM di Bank NTB Syariah KC Selong - fathurrazak, Fathurrazak; Hidayati MZ, Hikmatul; Jois Erlina, Baiq (Fakultas Syariah IAI Hamzanwadi Pancor, Lombok Timur, Indonesia, 2025)
This study is entitled Effectiveness of QRIS Transaction Services for MSMEs at BANK NTB Syariah KC Selong, the purpose of this study is to determine the application of digitalization to the QRIS system and to determine the effectiveness of the digitalization system for MSMEs with QRIS transactions. The approach used in this study is a qualitative descriptive approach. The descriptive approach is a study to determine facts with the right interpretation to recognize phenomena and to describe or accurately describe the characteristics of several phenomena, groups or individuals that are occurring. Data processing is a process that changes raw data into useful and easily accepted information. Data processing techniques are a series of steps or processes carried out to organize, clean, analyze, and interpret data collected in the study. Based on the results of the research and analysis that have been presented above, the researcher concludes that the QRIS service at Bank NTB Syariah KC Selong is a QRIS mobile application service provided by the bank that can be used by users or merchants to serve non-cash transactions by customers and non-customers of Bank NTB Syariah KC Selong. 1. The implementation of QRIS transactions based on a SWOT analysis of the QRIS transaction service at Bank NTB Syariah KC Selong shows that the implementation of the QRIS service at Bank NTB Syariah KC Selong has strengths such as complete application features, no administration fees, fast and easy transactions, and meets all transaction needs. However, it also has weaknesses such as transaction limits, registration can only be done at the office, only for users domiciled in NTB, and lack of socialization about the QRIS service. There are opportunities in this QRIS service which include, a fairly wide marketing coverage, the rapid growth of MSMEs in NTB, a comparison of the number of young people who are more than the old age in NTB, and strong support from the government. And this QRIS service has threats including, competition, limited information, old-fashioned people's mindsets, and internet networks that are still lacking. 2. The effectiveness of the QRIS transaction service for MSME actors through the QRIS transaction at Bank NTB Syariah KC Selong, namely it is said to be effective for MSME actors because it has several indicators such as ease of use, transaction security and being able to track sales. Then it is said to be ineffective for UMKM actors using the QRIS service of Bank NTB Syariah KC Selong because of several indicators such as technological accessibility, lack of public knowledge and understanding of QRIS and customer preferences.